The Relationship and Influence of Coaching Leadership Style in Training Program towards Student Athletesâ Satisfaction - Din, Anuar; Rashid, Salleh Abd; Noh, Siti Ajar Mohd (ASPENSI, 2015)
ABSTRACT: This study aims to identify the relationship and influence of coaching leadership style during the implementation of training program towards the satisfaction of student athletes. A total number of 206 student athletes from two sports school in Malaysia were selected using the simple random sampling method. This research is a non-experimental qualitative study using a survey method in order to answer the objectives and hypothesis. A set of questionnaire for measuring the LSS (Leadership Scale for Sport) and the ASQ (Athlete Satisfaction Questionnaire) were used for this study. Pearson Correlation and Multiple Regression were used to test the null hypothesis at significance level of p < 0.05, while SPSS program version 19 was used to analyze the data collected. The findings show that there is a positive and significant correlation (r = .586, p < .05) between the leadership style of coaching from all dimensions with athletes satisfaction. These findings also show that the training and instruction dimension is a significant dominant influence (Î² = .68, t(206) = 13,497, p < .05) for coaching leadership style of athlete satisfaction. As a result, the factors such as training and instruction dimension in coaching leadership style need to be addressed by trainer during the implementation of training program. KEY WORD: Leadership style, athlete satisfaction, sports school, training and instruction, coaching, student athlete, and implementation of training program.INTISARI: âHubungan dan Pengaruh Gaya Kepimpinan Jurulatih dalam Program Latihan terhadap Kepuasan Atlet Pelajarâ. Kajian ini bertujuan untuk mengenal pasti hubungan dan pengaruh gaya kepimpinan jurulatih semasa pelaksanaan program latihan terhadap kepuasan atlet pelajar. Seramai 206 orang atlet pelajar dari dua buah sekolah sukan di Malaysia telah dipilih dengan menggunakan pensampelan rawak mudah. Kajian ini adalah satu kajian kuantitatif bukan eksperimen dengan menggunakan kaedah tinjauan untuk menjawab objektif dan hipotesis kajian. Satu set borang soalselidik bagi LSS (Skala Kempimpinan dalam Sukan) dan ASQ (Soalselidik Kepuasan Atlet) digunakan dalam kajian ini. Analisis statistik inferensi seperti Korelasi Pearson dan Regresi Pelbagai digunakan untuk menguji sembilan hipotesis nol pada aras signifikan p < 0.05. Program yang digunakan untuk menganalisis data adalah program SPSS versi 19. Dapatan kajian menunjukkan terdapat hubungan yang positif dan signifikan (r = .586, p < .05) antara gaya kepimpinan jurulatih dari semua dimensi dengan kepuasan atlet. Dapatan kajian juga menunjukkan dimensi latihan dan arahan merupakan pengaruh dominan yang signifikan (Î² = .68, t(206) = 13.497, p < .05)Â bagi gaya kepimpinan jurulatih terhadap kepuasan atlet. Oleh yang demikian, faktor seperti dimensi latihan dan arahan dalam gaya kepimpinan jurulatih perlu diberikan perhatian oleh jurulatih semasa melaksanakan program latihan.KATA KUNCI: Gaya kepimpinan, kepuasan atlet, sekolah sukan, latihan dan arahan, jurulatih, atlet pelajar, dan perlaksanaan program latihan.Â Â Â Â About the Authors: Dr. Anuar Din is a Senior Lecturer at the Faculty of Psychology and Education UMS (Malaysia University of Sabah), 88400 Kota Kinabalu, Sabah, Malaysia; Prof. Dr. Salleh Abd Rashid is a Lecturer at the Center of Human Development and Techno-Communication UNIMAP (Malaysia University of Perlis), 02600 Jejawi, Perlis, Malaysia; and Siti Ajar Mohd Noh is a Lecturer at the IPGM (Malaysia Institute of Teacher Education) Campus Gaya, Kota Kinabalu, Sabah, Malaysia. The authors can be contacted via e-mails address at: anudin@ums.edu.my, salleh@unimap.edu.my, and sitimdnoh@gmail.comHow to cite this article? Din, Anuar, Salleh Abd Rashid & Siti Ajar Mohd Noh. (2015). âThe Relationship and Influence of Coaching Leadership Style in Training Program towards Student Athletesâ Satisfactionâ in SIPATAHOENAN: South-East Asian Journal for Youth, Sports & Health Education, Vol.1(1) April, pp.125-138. Bandung, Indonesia: Minda Masagi Press, APAKSI Bandung, and KEMENPORA RI Jakarta, ISSN 2407-7348.Â Chronicle of the article: Accepted (February 13, 2015); Revised (March 15, 2015); and Published (April 21, 2015).